Critical Roles of STAT3 in β-Adrenergic Functions in the Heart - Zhang, Wenjun (Circulation, 2015)
BACKGROUND: β-adrenergic receptors (βARs) play paradoxical roles in the heart. On one hand, βARs augment cardiac performance to fulfill the physiological demands, but on the other hand, prolonged activations of βARs exert deleterious effects that result in heart failure. The signal transducer and activator of transcription 3 (STAT3) plays a dynamic role in integrating multiple cytokine signaling pathways in a number of tissues. Altered activation of STAT3 has been observed in failing heart in both the human patients and animal models. Our objective is to determine the potential regulatory roles of STAT3 in cardiac βAR-mediated signaling and function. METHODS AND RESULTS: We observed that STAT3 can be directly activated in cardiomyocytes by β-adrenergic agonists. To follow up this finding, we analyzed βAR function in cardiomyocyte-restricted STAT3 knockouts and discovered that the conditional loss of STAT3 in cardiomyocytes markedly reduced the cardiac contractile response to acute βAR stimulation, and caused disengagement of calcium coupling and muscle contraction. Under chronic β-adrenergic stimulation, Stat3cKO hearts exhibited pronounced cardiomyocyte hypertrophy, cell death, and subsequent cardiac fibrosis. Biochemical and genetic data supported that Gαs and Src kinases are required for βAR-mediated activation of STAT3. Finally, we demonstrated that STAT3 transcriptionally regulates several key components of βAR pathway, including β(1)AR and PKA, and T-type Ca(2+) channels. CONCLUSIONS: Our data demonstrates for the first time that STAT3 has a fundamental role in βAR signaling and functions in the heart. STAT3 serves as a critical transcriptional regulator for βAR-mediated cardiac stress adaption, pathological remodelling and heart failure.